PELAYANAN KESEHATAN PUSKESMAS APUNG DI PULAU PELAPIS KECAMATAN KEPUALAUAN KARIMATA KABUPATEN KAYONG UTARA - Tri Ardiansyah E.42009073 (FISIP Universitas Tanjungpura Pontianak, 2021)
The purpose of this study is to describe and analyze the implementation of health service Puskesmas Apung in Kecamatan Kepuasaan Karimata Kabupaten Kayong Utara. This study using a qualitative approach for describe overall implementation of health service. Data was collected by using interview technic and documentation. The research sites in Pulau Pelapis Kecamatan Kepulauan Karimata Kabupaten Kayong Utara. The condusions from this studies shows that health service which gives by Puskesmas Apung not maximal, this is caused by there are some residents who complained less than the maximum of health service Puskesmas Apung so that residents who want to get service everytime be inhibited. Recommendations of this study in order to implementations of health service can be a maximum must have one boat of Puskesmas Apung again for serve the local people Kepulauan Karimata.Keyword : Health Service and Puskesmas Apung.